A Morpho-Syntactic Error Analysis of Students‘ Writing at the State Madrasah Tsanawiyah of Sukoharjo - Bayu Nandra Ramadhan (Universitas Islam Negeri (UIN) Mataram, 2018)
English is considered as an Indonesian students‘ foreign language which is not used frequently in their daily conversations. Since writing in English is a challenging experience for Indonesian students, they sometimes commit errors in grammar and sentence structures. Learners‘ errors were considered as the best sources to identify students‘ writing skills deficiency. They can be useful for teachers, learners, textbook providers, education system and so on. This descriptive qualitative research investigated the Indonesian EFL linguistics taxonomy of morpho-syntactic errors and the sources of the errors. The participants of the study were the third graders of the State Madrasah Tsanawiyah Sukoharjo. They were asked to write a descriptive text about their mother. After collecting the data and categorizing and identifying the erroneous areas in their work, the data were analysed using the linguistic taxonomy of errorscoined by Keshavarz (2006). The results of this study showed that the most frequent part of the students‘ errors based on morpho-syntactical errors was